The pathogenic mechanisms of Tilletia horrida as revealed by comparative and functional genomics. Issue 1 (December 2018) - Wang, Aijun; Pang, Linxiu; Wang, Na; Ai, Peng; Yin, Desuo; Li, Shuangcheng; Deng, Qiming; Zhu, Jun; Liang, Yueyang; Zhu, Jianqing; Li, Ping; Zheng, Aiping
Abstract Tilletia horrida is a soil-borne, mononucleate basidiomycete fungus with a biotrophic lifestyle that causes rice kernel smut, a disease that is distributed throughout hybrid rice growing areas worldwide. Here we report on the high-quality genome sequence ofT. horrida ; it is composed of 23.2 Mb that encode 7, 729 predicted genes and 6, 973 genes supported by RNA-seq. The genome contains few repetitive elements that account for 8.45% of the total. Evolutionarily, T. horrida lies close to theUstilago fungi, suggesting grass species as potential hosts, but co-linearity was not observed betweenT. horrida and the barley smutUstilago hordei . Genes and functions relevant to pathogenicity were presumed.T. horrida possesses a smaller set of carbohydrate-active enzymes and secondary metabolites, which probably reflect the specific characteristics of its infection and biotrophic lifestyle. Genes that encode secreted proteins and enzymes of secondary metabolism, and genes that are represented in the pathogen-host interaction gene database genes, are highly expressed during early infection; this is consistent with their potential roles in pathogenicity. Furthermore, among the 131 candidate pathogen effectors identified according to their expression patterns and functionality, we validated two that trigger leaf cell death inNicotiana benthamiana . In summary, we have revealed new molecular mechanisms involved in the evolution, biotrophy, and pathogenesis ofT. horrida .